Influence of a graphene oxide additive and the conditions of membrane formation on the morphology and separative properties of poly(vinylidene fluoride) membranes. Issue 46 (21st August 2015) - Fryczkowska, Beata; Sieradzka, Marta; Sarna, Ewa; Fryczkowski, Ryszard; Janicki, Jarosław
ABSTRACT In this article, we present our study of the influence of a graphene oxide (GO) additive and the method of preparation on the properties of membranes. Poly(vinylidene fluoride) (PVDF)/GO membranes were obtained by an inverse phase method, which was conducted by two different methods. The first one was based on solvent evaporation, and the second method was a coagulation bath in distilled water. Our studies clearly showed that the introduction of the GO nanoadditive into the polymer membrane matrix played a major role in the pore process formation, and it also contributed to the reduction of the contact angle, and this led to an improvement in the hydrophilic properties of the obtained membranes. Furthermore, the PVDF/GO membrane preparation process had a direct influence on the thickness and porosity. Both of these factors had a direct influence on the transport properties of the membrane. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42789.